TINJAUAN PENANGANAN LINEN KAMAR OLEH LAUNDRY SECTION PADA SAAT HIGH OCCUPANCY DI HOTEL HILTON BANDUNG - Fatimah Azzahra; Della Sari, Windy; Afriadi (Jurnal Pariwisata Bunda, 2023)
This article reports the results of research on the handling of room linen in the laundry section. Handling linen during High Occupancy must really be a priority so that the completeness of the room can be fulfilled. This study used a descriptive method, with data collection techniques through observation of handling room linen with laundry at Hilton Hotel Bandung. The results showed that the handling of room linen in the laundry section of Hilton Bandung Hotel has run well and smoothly starting from controlling linen, handling damaged linen, replacing dirty and clean linen, recording for each linen exchange,  washing dirty linen process, washing temperature applied, handling linen contaminated with dust and blood stains, and handling linen when High Occupancy occurs. Then in carrying out the procedures in the laundry carried out in accordance with the standards set by the Hilton Bandung hotel.